1994
DOI: 10.1177/154079699401900202
|View full text |Cite
|
Sign up to set email alerts
|

Easy for you to Say: Teacher Perspectives on Implementing Most Promising Practices

Abstract: Difficulties in translating innovations that have been validated by researchers into practices that will be used by practitioners are widely acknowledged. Nevertheless, research on systems change is sparse and teachers are seldom asked for their perspectives on the implementation of innovations. Special education teachers (n = 83) from five states in regions known for their efforts to develop quality educational programs for students with severe disabilities were surveyed for their knowledge and skills, the ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
50
1

Year Published

1996
1996
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(52 citation statements)
references
References 13 publications
1
50
1
Order By: Relevance
“…Two common barriers are a lack of time to implement programs and inadequate support from administrators (Ayres, Meyer, Erevelles, & Park-Lee, 1994;Klingner et al, 1999;Stanovich & Stanovich, 1997;Taylor et al, 1999). Another barrier is a lack of materials.…”
Section: Overcoming Barriers To Implementing New Practicesmentioning
confidence: 96%
“…Two common barriers are a lack of time to implement programs and inadequate support from administrators (Ayres, Meyer, Erevelles, & Park-Lee, 1994;Klingner et al, 1999;Stanovich & Stanovich, 1997;Taylor et al, 1999). Another barrier is a lack of materials.…”
Section: Overcoming Barriers To Implementing New Practicesmentioning
confidence: 96%
“…In a study of the turnover rate among special education teachers in Maine (USA), Bretherton and Donaldson (1991) reported that teachers who left their jobs perceived lack of support from school management and a lack of administrative support in everyday teaching. Ayres et al (1994) studied the needs of special education teachers of students with severe and profound impairments in ve states in the USA. Their ndings revealed that teachers experienced two types of barriers: lack of time and lack of support from school management.…”
Section: Child Characteristics In Uencing the Classroom Systemmentioning
confidence: 99%
“…They postulated that changes in teachers' roles and reallocation of time and resources may be necessary to reduce the gap. Ayres, Meyer, Erevelles, and Park-Lee (1994) surveyed special education teachers about the difficulties of implementing validated practices in classrooms and found that teachers reported lack of time and lack of administrative support as barriers to implementation. They speculated that many schools do not have the financial or community support to do more than maintain existing services.…”
mentioning
confidence: 99%